2005
DOI: 10.1161/01.res.0000152967.88472.3e
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Melastatin 7 Ion Channels Regulate Magnesium Homeostasis in Vascular Smooth Muscle Cells

Abstract: Abstract-Magnesium modulates vascular smooth muscle cell (VSMC) function. However, molecular mechanisms regulating VSMC Mg 2ϩ remain unknown. Using biochemical, pharmacological, and genetic tools, the role of transient receptor potential membrane melastatin 7 (TRPM7) cation channel in VSMC Mg 2ϩ homeostasis was evaluated. Rat, mouse, and human VSMCs were studied. Reverse transcriptase polymerase chain reaction and immunoblotting demonstrated TRPM7 presence in VSMCs (membrane and cytosol). Angiotensin II (Ang I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(171 citation statements)
references
References 57 publications
(65 reference statements)
4
165
0
1
Order By: Relevance
“…We showed that, in vascular cells, magnesium influx is driven mainly through TRPM7-sensitive pathways and that an altered cellular magnesium homeostasis and abnormal vascular smooth muscle cell function in hypertension may be, in part, related to defective TRPM7 expression/activity. 15,16 To further explore the pathophysiological significance of these findings, we used a model of inherited hypomagnesemia to investigate the effects of chronic magnesium deficiency on microvascular structure and function, magnesium transporter (TPRM7) expression, and vascular inflammatory status. Using bidirectional selective breeding, mice from a heterogenous population were selected for low (MgL) and normal-high (MgH) levels of erythrocyte magnesium.…”
mentioning
confidence: 99%
“…We showed that, in vascular cells, magnesium influx is driven mainly through TRPM7-sensitive pathways and that an altered cellular magnesium homeostasis and abnormal vascular smooth muscle cell function in hypertension may be, in part, related to defective TRPM7 expression/activity. 15,16 To further explore the pathophysiological significance of these findings, we used a model of inherited hypomagnesemia to investigate the effects of chronic magnesium deficiency on microvascular structure and function, magnesium transporter (TPRM7) expression, and vascular inflammatory status. Using bidirectional selective breeding, mice from a heterogenous population were selected for low (MgL) and normal-high (MgH) levels of erythrocyte magnesium.…”
mentioning
confidence: 99%
“…Altered cellular Mg 2+ homeostasis and abnormal VSMC function in hypertension may be related to defective TRPM7 expression/ activity [65,66]. Touyz et al [67] demonstrated that TRPM7 was present and functionally active in human, mouse and rat VSMCs. Furthermore, they found that TRPM6 was unaltered in SHR, but expression of TRPM7 was blunted.…”
Section: Trp Channel Subtypes M and V Have Antihypertensive Effectsmentioning
confidence: 99%
“…TRPM7 or TRP-PLIK (transient receptor potentialphospholipase interacting kinase) is widely expressed in tissues including vascular smooth muscle and endothelium [31]. It is a 105pS outward rectifier and is permeable to Na + and Ca 2+ .…”
Section: Trpm7mentioning
confidence: 99%